Electro-encephalographic features and electro-clinic associations in children with migraine: A possible relationship with epilepsy - Pérez Galdós, Proel (2024)
Objective: To determine the clinical characteristics and EEG-associated features in children with migraine. Patients and methods: This is an observational and analytical study. Fifty-two patients 4-14 years of age were selected, who fulfilled criteria for diagnosing migraine in children (ICHD-II) during 2010. A surface EEG was performed in every child, including photo-stimulation (PS) and hyperventilation (HV), during the interictal period. We used the chi-square method for the statistical analysis. Results: The average age was 10.1 years, 53.8% were male, 32.7% had pulsátiles headache, nausea/vomiting were present in 26.9%, photophobia and sonophobia in 11.5%, and visual aura in 3.8%. The altered EEG patterns were as follows: diffuse slow-down waves in 13.5%, theta-delta wave outbreaks during PS and HV in 34.6%, and interictal epileptiform discharges (IED) were present in 19.2%. The electro-clinical association was significant in the 4-9 year-old population reactive to PS (p= 0.005), as well as in those male subjects who developed theta-delta wave outbreaks (p=0.03), and IEDs were more prevalent in female subjects (p=0.046). Conclusions: The electro-clinic association was significant during PS and HV in these 4-9 year-old children, particularly in males, and IED were predominant in females.